EFFECTS OF NUTRITION AREA ON THE FRUIT INDEX IN THE PRIMARY SEED PRODUCTION OF WATERMELON - E. A. Varivoda; T. G. Koleboshina; N. G. Baybakova; N. V. Kobkova; D. S. Shaposhnikov (Овощи России, 2018)
The basis for increasing the production of vegetables and melons is to obtain high-quality seeds of high reproductions. This will ensure the implementation and stability of breeding characteristics of varieties, the preservation of economic and valuable features. To solve these tasks, it is necessary to transfer the industry to a new, more modern level of seed production. The studies were conducted using the methods of individual and individual-family selection with evaluation by offspring, using the method of "halves" through control and elite nurseries. The method of production of elite and original seeds is developed. Conducted research to improve schemes of sowing of gourds with the study of the influence of space power to approbation the signs of varieties with different index of fruits. By reduction of the nutrition area per plant to 2.1 sq m2 in the variety of watermelon Icarus the yield of seeds increased 1.5-1.9 times in comparison with the standard number of fruits with an index of <1.0 was 8.2%. The thickening of the crop did not have a noticeable effect on the shape of the fruit. A watermelon with a broadly elliptical shape of the fruit, variety Volzhanin observed dependence of the shape of the fruit from planting schemes. With the reduction of the nutrition area up to 2.1 m2 number of fetuses with index >1.5 28.2% in the second generation, the seed yield was 111.9 kg/ha. The change in the index of the foetus has led to a significant change in varietal characteristics, which is unacceptable in the primary seed production. Reducing the area of nutrition in watermelon varieties with spherical and rounded shape allowed to increase the yield of seeds without affecting the varietal characteristics.